Heat-resistant alloy and its manufacturing method

The heat-resistant alloy addresses intergranular corrosion and mechanical property issues by incorporating specific elements like Mg, B, Mo, Ca, and REM, resulting in enhanced corrosion resistance and maintained mechanical properties post-pickling.

JP7657394B1Active Publication Date: 2025-04-04NIPPON YAKIN IND KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2025005619
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-04
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

Existing heat-resistant alloys face challenges with intergranular corrosion resistance and mechanical property deterioration after welding and pickling, particularly due to erosion of grain boundaries.

Method used

A heat-resistant alloy composition is developed with controlled sulfur content, addition of magnesium (Mg), boron (B), and molybdenum (Mo), along with calcium (Ca) and rare earth metals (REM), to enhance intergranular corrosion resistance and maintain mechanical properties post-pickling.

Benefits of technology

The alloy exhibits improved intergranular corrosion resistance and maintains mechanical properties after pickling, reducing the risk of grain boundary erosion and crack propagation, thus ensuring structural integrity in heat-resistant applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657394000001_ABST
    Figure 0007657394000001_ABST
Patent Text Reader

Abstract

Provided is a heat-resistant alloy whose mechanical properties are less likely to deteriorate after welding. [Solution] The heat-resistant alloy has a composition containing, on a mass basis, C: 0.001 to 0.050%, Si: 0.05 to 0.70%, Mn: 0.10 to 1.0%, P: 0.035% or less, S: 0.0013% or less, Cr: 19.0 to 25.0%, Mo: 2.00 to 4.00%, Cu: 1.0 to 3.5%, Ti: 0.10 to 1.50%, Al: 0.01 to 0.50%, B: 0.0001 to 0.0060%, Fe: 22.0 to 40.0%, Mg: 0.0003 to 0.0180%, N: 0.020 or less, and O: 0.0050% or less, with the balance being Ni and unavoidable impurities, and the composition satisfies the relationship 100Mg-2500S≧-1.5.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a heat-resistant alloy having excellent mechanical properties and a manufacturing method thereof, and in particular to a heat-resistant alloy having excellent weldability. In this specification, "x to y" representing a range of values ​​means "x or more and y or less" and includes the boundary value. The unit of mass "t" represents 1000 kg. [Background technology]

[0002] Many Ni-based alloys are used for heat-resistant applications, and strength is important. In addition, since they are used as equipment components and structures, they are almost always welded. After welding, they are pickled to remove oxide scale. In some cases, they are annealed to remove distortion from welding before pickling, and then pickled.

[0003] Heat-resistant alloys may also be used as clads with ordinary steel. When joining by explosive bonding, etc., stress relief annealing is also required, and in this case, oxide scale forms on the surface, so it must be removed by pickling. Among heat-resistant alloys, the oxide scale of high heat-resistant alloys containing Cr is particularly dense, and long pickling times are required to remove it.

[0004] On the other hand, heat-resistant alloys are excellent in heat resistance, but are not excellent in acid resistance. Furthermore, the solid solubility of C is not large, and the alloy composition is easily sensitized. That is, considering the above process, pickling is often performed in a sensitized state, and rough surfaces may occur due to erosion of grain boundaries. In particular, when welding is performed, the grain boundaries of the welded parts are often eroded further.

[0005] In other words, structures made of heat-resistant alloys are operated in a state where the grain boundaries are eroded, and it is necessary to ensure strength characteristics even when there are mechanical weaknesses on the surface that can become the starting point of cracks due to erosion, etc. In other words, heat-resistant alloys need to have both grain boundary corrosion resistance and grain boundary strength.

[0006] For example, Patent Document 1 proposes a Ni-based alloy with excellent surface cleanliness, in which Mg and Ca are added in the form of an alloy to fix S. Patent Document 2 discloses an alloy that has excellent resistance to hot cracking in welds by controlling the S concentration in inclusions and fixing S. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent Publication No. 2021-070838 [Patent Document 2] JP 2022-163586 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, the above-mentioned conventional techniques have the following problems. That is, the alloy disclosed in Patent Document 1 does not take into consideration the corrosion resistance of grain boundaries or the mechanical properties after pickling. The alloy described in Patent Document 2 takes into consideration cracking during welding, but does not take into consideration the corrosion resistance after welding.

[0009] Therefore, an object of the present invention is to provide a heat-resistant alloy in which mechanical properties resulting from the surface shape or metal structure are unlikely to deteriorate even if pickling is performed after welding, and further, to provide a heat-resistant alloy in which the base metal has excellent resistance to intergranular corrosion. [Means for solving the problem]

[0010] The inventors have conducted intensive research to solve the above problems. In particular, they have focused on the relationship between the S content and intergranular corrosion. They have found that fixing S by Mg is useful for reducing the amount of dissolved S as much as possible at an industrial level. In addition, they have found that it is effective to estimate the amount of sulfide in the material, take the ratio to the total S, and keep the ratio within a certain value, focusing on the fact that it is not only the total S that should be controlled but also the dissolved S. They have also found that it is effective to estimate the amount of sulfide in the material, take the ratio to the total S, and keep the ratio within a certain value. They have also found that by fixing S and then adding an appropriate amount of B, the intergranular corrosion resistance is improved, the strength of the grain boundaries is increased, and even if some erosion of the grain boundaries occurs due to pickling, cracks are less likely to progress in a tensile test. They have also found that by fixing S and then adding an appropriate amount of B and Mo, the corrosion resistance of the grain boundaries is improved. They have also found that although the fixation of S is effective even with the addition of Mg alone, the addition of at least one of Ca and REM suppresses the grain boundary erosion of the bead portion and makes it difficult for cracks to progress due to tensile stress. From the above, they have developed the present invention.

[0011] The heat-resistant alloy according to the present invention, which advantageously solves the above problems, comprises, on a mass basis, C: 0.001 to 0.050%, Si: 0.05 to 0.70%, Mn: 0.10 to 1.0%, P: 0.035% or less, S: 0.0013% or less, Cr: 19.0 to 25.0%, Mo: 2.00 to 4.00%, Cu: 1.0 to 3.5%, Ti: 0.10 to 1.50%, Al: 0.01 to 0.50%, B: 0.0001 to 0.0060%, Fe: The composition of the present invention is characterized in that it contains 22.0 to 40.0%, Mg: 0.0003 to 0.0180%, N: 0.020 or less, and O: 0.0050% or less, and optionally contains at least one selected from Ca: 0.00001 to 0.00500% and REM: 0.00001% to 0.00500%, with the balance being Ni and unavoidable impurities, and that the composition satisfies the following relational formula (1): [Equation (1)] 100Mg-2500S≧-1.5 Here, the element symbols in the above formula indicate the content of each element in mass %.

[0012] The heat-resistant alloy according to the present invention is (a) Total S content (%S) based on mass percentage and 1mm 2 The sulfide amount SS calculated by multiplying the number density of sulfides per unit area by the square of the sulfide diameter in mm satisfies the following relational expression (2). (b) the above-mentioned composition satisfies the following relational formula (3): (c) the above-mentioned composition satisfies the following relational formula (4): (d) containing at least one of Ca and REM, and the above-mentioned composition satisfies the following relational formula (5); This is a more preferable means of solving the problem. [Equation (2)] (%S) / SS<100 [Equation (3)] 100Mg+220B-2500S≧-1.2 Here, the element symbols in the above formula indicate the content of each element in mass %. [Equation (4)] Mo+0.61×lnB ≧-2.0 Here, the element symbols in the above formula represent the content of each element in mass%. ln is the logarithm function (natural logarithm). [Equation (5)] 100Mg+500Ca+400REM-2500S≧-1.3 Here, the element symbols in the above formula indicate the content of each element in mass %.

[0013] The present invention provides a method for producing a heat-resistant alloy that advantageously solves the above-mentioned problems, comprising the steps of: adjusting an alloy composition by heating and melting an alloy raw material, followed by refining; casting the obtained molten alloy to obtain a slab; hot rolling the obtained slab to obtain a hot-rolled alloy plate; and optionally cold rolling the hot-rolled alloy plate to obtain a cold-rolled alloy plate; in the refining, a mixed gas of oxygen gas and argon gas is blown into the heated and melted alloy raw material to decarburize it and control the nitrogen content to 0.01 mass% or less, followed by Cr reduction; and then adding a CaO source containing aluminum and fluorite to the molten alloy to form a CaO-SiO2-Al2O3-MgO-F-based slag, and then optionally adding a raw material containing REM. Effect of the Invention

[0014] The heat-resistant alloy of the present invention is suitable for use in structures for heat-resistant applications, since its mechanical properties resulting from its surface shape or metal structure are unlikely to deteriorate even if it is subjected to pickling after welding. [Brief description of the drawings]

[0015] [Figure 1] 1 is a graph showing the effects of S and Mg on intergranular corrosion of a heat-resistant alloy according to an embodiment of the present invention. [Diagram 2] 2 is a graph showing the effect of the total S content, which is an index value of solute S, divided by the amount of sulfide on the intergranular corrosion of the heat resistant alloy. [Diagram 3] 2 is a graph showing the effects of S and B on intergranular corrosion of the base metal after welding of the above heat-resistant alloy. [Figure 4] 4 is a graph showing the effect of Mg and composite additive elements on intergranular corrosion of a bead portion after welding of the above heat-resistant alloy. [Diagram 5] 4 is a graph showing the effect of the composition of contained elements and the effect of the index value of solute S on the tensile strength ratio before and after pickling for a test piece after welding of the above heat-resistant alloy. [Figure 6] 2 is a graph showing the effect of combined addition of Mo and B on mechanical properties of a test piece after welding of the above heat-resistant alloy. [Figure 7] 4 is a graph showing the effect of the composition of contained elements on the tensile strength ratio before and after pickling for a test piece of the above heat-resistant alloy after welding. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The circumstances that led to the development of the present invention will now be described. The inventors have focused on reducing the content of solute S, which primarily promotes intergranular corrosion.

[0017] (Experiment 1) An alloy was prepared with the composition shown in Table 1, with the remainder consisting of Ni and unavoidable impurities. This alloy contains C, Si, and Mn, with the target of Cr: 22 mass%, Fe: 30 mass%, and Mo: 2%. In preparing the alloy, the relationship between the amount of Mg added and corrosion was investigated for the addition of S: 0.001 mass% and no addition. The alloy was prepared by melting the raw metal in a magnesia crucible in air using a high-frequency induction furnace. After desulfurization with CaO-Al2O3-MgO-F slag, it was cast in a mold to obtain a 20 kg ingot. This ingot was hot-rolled to obtain a hot-rolled alloy sheet. The obtained hot-rolled alloy sheet was annealed, pickled, and cold-rolled to obtain a cold-rolled alloy sheet with a thickness of 2 mm. The obtained cold-rolled alloy sheet was annealed at 1150°C. The composition of C and S in Table 1 was measured using a carbon-sulfur simultaneous analyzer based on the oxygen flow combustion-infrared absorption method. Other elements were analyzed using an X-ray fluorescence analyzer. The S content in Table 1 is the "total S" value, including not only the S employed in the alloy, but also the S in compounds and nonmetallic inclusions. The lower limit "-" indicates that it is not intentionally added, and allows for the inclusion of a small amount that is unavoidable.

[0018] [Table 1]

[0019] The cold-rolled alloy sheets after the annealing were collected as test pieces. The test pieces were polished and subjected to the ASTM G28A intergranular corrosion test. The test results are shown in Figure 1. The corrosion ratio of the material without Mg was set as the standard, at 1.0, and the effect of Mg addition on the corrosion ratio with and without S is shown in Figure 1. In Figure 1, the vertical axis represents the corrosion ratio, and the horizontal axis represents the content of Mg as the target element.

[0020] From the results in Figure 1, in materials without added S, no effect of the addition of Mg was observed on intergranular corrosion resistance within the test range. On the other hand, in alloy plates containing 0.001 mass% S, it was found that the more Mg was added, the better the intergranular corrosion resistance became within the test range. The reason for this is thought to be that the addition of Mg turns S into sulfides, reducing the amount of dissolved S, and in particular, reducing the amount of S segregated at grain boundaries, improving intergranular corrosion resistance. This can also be understood from the fact that sulfides are observed in the metal structure when observing the metal structure of alloy plates with added Mg.

[0021] From the above results, it was thought that it would be effective not only to reduce the total S content but also to reduce the dissolved S content in the alloy. Therefore, as an index that quantitatively indicates the content of dissolved S, an index was used in which the total S (%S) is divided by the amount of sulfide SS. Specifically, the following relational formula (2A) is used. [Equation (2A)] (%S) / SS = (%S) / [sulfide number density (pieces / mm 2 ) × (sulfide diameter) 2 ] The number density of sulfides and the diameter of sulfides in the above formula can be calculated as follows.

[0022] <Identification of sulfides> The cross section parallel to the rolling direction was polished to a mirror finish and subjected to SEM-EDS particle analysis. 2 The area of ​​the particles was evaluated. Three random fields of view were observed within an area of ​​1 mm x 3 mm. When counting the number of sulfides, oxides and sulfides can be detected because their brightness is clearly different from that of the metal substrate. Only particles with an S concentration of 0.5% or more were counted as sulfides by point analysis of the extracted particles.

[0023] <Size of sulfide> The size of the sulfides was calculated as follows. Thirty sulfides detected by the above particle analysis were randomly selected, and the range of S was detected from a 20,000x mapping image. Separately, secondary electron images and composition images were taken, and the area where S was detected was identified, surrounded, and calculated as the equivalent circle diameter. The average of the 30 equivalent circle diameters was taken as the "sulfide diameter." This process allows the calculation of the equivalent circle diameter from the area containing only sulfides, even when evaluating composite inclusions composed of sulfides and oxides.

[0024] FIG. 2 shows the relationship between (%S) / SS calculated by the relational expression (2A) as an index of solute S and the corrosion ratio. The corrosion ratio in FIG. 2 is expressed as 1.0, which is the corrosion ratio of a test piece in which the elements other than S and Mg are not added and the composition is adjusted to the same range as in Table 1. The values ​​in the figure are the total S values ​​expressed in mass %. From the results in FIG. 2, it can be seen that the intergranular corrosion resistance depends not on the total S content but on the solute S content. In other words, the intergranular corrosion resistance of the alloy according to this embodiment can be improved by fixing S to sulfides and the like to reduce the amount of solute S.

[0025] (Experiment 2) As in Experiment 1, an alloy plate was produced by melting an alloy containing the components shown in Table 2. In this experiment, the effects of adding B and the effects of adding Ca and REM, which have the same S adhesion as Mg, were confirmed.

[0026] [Table 2]

[0027] The cold-rolled alloy sheets obtained in the same manner as in Experiment 1 were butted together and TIG welded, and test pieces were taken so as to include the welded zone and the heat-affected zone. The test pieces were subjected to the ASTM G28A intergranular corrosion test. In this experiment, the effect of each element on intergranular corrosion resistance and its relationship with welding were investigated. The welding conditions were as follows: no filler metal was used, TIG welding, I groove, welding current was 150A, welding speed was 250cm / min, and Ar gas was used as shielding gas on both the front and back sides.

[0028] The intergranular corrosion depth of the bead and base material of the test pieces after the ASTM G28A intergranular corrosion test was measured. A reference material without added S or target elements was tested in the same way, and its corrosion depth was set to 1.0, and the corrosion depth ratio was normalized for evaluation. Note that there were test pieces in which bead defects occurred and defects remained even after cutting and polishing to the size required for the corrosion test pieces, but the corrosion test was carried out in the defective state. Even when the defective part corroded, the corrosion depth was measured.

[0029] <Corrosion of base material> The corrosion depth ratio of the base material is summarized by the B content in Fig. 3. In the case of the alloy of this embodiment in which no S was added, the intergranular corrosion resistance of the base material deteriorated with the addition of B. The inventors speculate that this is because B segregated at the grain boundaries and promoted corrosion.

[0030] On the other hand, when 0.001 mass% S was added, the addition of a small amount of B improved the intergranular corrosion resistance, while the addition of excessive B deteriorated the intergranular corrosion resistance. The inventors speculate that this mechanism is as follows. Solute S and B compete for segregation to grain boundaries, and the addition of a small amount of B reduces the amount of solute S segregated to grain boundaries, improving intergranular corrosion resistance. On the other hand, the addition of excessive B increases the amount of B segregated to grain boundaries, canceling out the effect of solute S in reducing segregation, thereby deteriorating intergranular corrosion resistance.

[0031] From these results, it can be seen that after reducing the amount of dissolved S with elements that easily form sulfides, such as Mg, adding an appropriate amount of B can further improve intergranular corrosion resistance. In addition, when 0.001 mass% S was added and then fixed with Mg, and Mo was also included, the effect of containing B became more pronounced. The higher the Mo content, the more effective the addition of a small amount of B was. Mo is an element that is effective in acid resistance, and it is speculated that the presence of B causes it to co-segregate at the grain boundaries, increasing the grain boundary Mo concentration.

[0032] <Corrosion of the bead> Next, the corrosion depth ratio of the bead part is shown in Fig. 4 in relation to the sum of the contents of the added elements. First, when Mg was added alone, an improvement in intergranular corrosion resistance was observed even in the bead part. However, the effect was saturated when a certain amount was added. It is considered that the sulfide MgS formed was decomposed by the heat during welding, and the solid-solution S segregated again to the grain boundary. In addition, since Mg has a low boiling point, the excessive addition of Mg may cause Mg vapor to be generated by the welding heat, which may cause welding defects such as black spots and blisters in the bead. Corrosion progresses from such welding defects. Therefore, the addition of excessive Mg deteriorates the corrosion resistance of the welded part.

[0033] The alloys containing B in addition to Mg showed a further improvement in intergranular corrosion resistance even in the region where the effect of improving intergranular corrosion resistance was saturated with the addition of Mg alone. This is presumably because when S re-dissolved due to the decomposition of sulfides segregates to the grain boundaries, it competes with B, which also segregates to the grain boundaries, reducing the amount of S segregating to the grain boundaries in the bead section.

[0034] Furthermore, by adding Ca or REM, which form sulfides, together with Mg, the effect of improving intergranular corrosion resistance was further improved in the region where the effect of improving intergranular corrosion resistance was saturated by adding Mg alone. Here, REM stands for rare earth elements, and refers to 17 elements including Sc, Y, and lanthanides. By adding one element selected from Ca and REM in addition to Mg, the corrosion depth of the bead part became shallower. The reason for this is presumed to be that the sulfides of Ca and REM are thermodynamically more stable than those of Mg, and are less likely to decompose due to the heat during welding.

[0035] (Experiment 3) Test pieces were taken from the alloy plates and welded test pieces prepared in Experiments 1 and 2. Since oxide scale forms on the surface after welding, the test pieces were immersed in nitric hydrofluoric acid to completely descale the surface. The immersion conditions in nitric hydrofluoric acid were a mixed solution of 1.5M nitric acid and 1.5M hydrofluoric acid at 50°C for 48 hours.

[0036] Tensile test pieces according to JIS 13B were taken from the test materials before and after pickling. The test pieces were taken so that the tensile direction and the welding direction were perpendicular to each other. The test pieces were taken so that the welded part was at the center of the longitudinal direction of the tensile test pieces. The test pieces before and after pickling were subjected to tensile tests to calculate the tensile strength. The degree of deterioration of mechanical properties due to pickling was judged by normalizing with the tensile strength of the test pieces before pickling. Hereafter, the normalized tensile strength = tensile strength of the test pieces after pickling / tensile strength of the test pieces before pickling is called the "TS ratio". The results are plotted in Figures 5 to 7. The symbols "◎" and "◇" in the figures indicate that the TS ratio is greater than 0.90 and that there is almost no deterioration of mechanical properties due to pickling. The symbols "〇" and "□" indicate that the TS ratio is in the range of 0.70 to 0.90 and that there is little deterioration of mechanical properties due to pickling. The symbol "x" indicates that the TS ratio is less than 0.70, and that the mechanical properties have deteriorated due to pickling.

[0037] Excessive S content caused significant grain boundary erosion during pickling, and in tensile tests, fracture occurred at the grain boundary eroded area with low tensile strength. Depending on the S content, the addition of Mg reduced the amount of dissolved S, inhibited grain boundary erosion, and inhibited the decrease in TS ratio. The plots "◎", "◯", and "×" in Figure 5 represent the results for the addition of Mg alone. The horizontal axis is the S content, and the first vertical axis (left side) is the Mg content.

[0038] First, the following relational expression (1) was found as a condition for minimizing deterioration of mechanical properties due to pickling. [Equation (1)] 100Mg-2500S≧-1.5 Here, the element symbols in the formula indicate the content of each element in mass %.

[0039] In addition, the following relational expression (6) was found as a condition for causing almost no deterioration in mechanical properties due to pickling. [Equation (6)] 100Mg-2500S≧-1.2 Here, the element symbols in the formula indicate the content of each element in mass %.

[0040] The numbers added to the plots in Fig. 5 are indices of dissolved S calculated by the above-mentioned relational expression (2A). Even within the range satisfying the above-mentioned relational expression (1), there was a range where the symbol "◎" indicated that there was almost no deterioration in mechanical properties due to pickling when the following relational expression (2) was satisfied between the total S content (%S) and the amount of sulfide SS. [Equation (2)] (%S) / SS<100 Here, (%S) is the total S content based on mass%, and SS is the total S content based on mass%. 2 The amount of sulfides is calculated by multiplying the number density of sulfides per unit area by the square of the sulfide diameter in mm.

[0041] The plots "◇" and "□" in Figure 5 represent examples of combined addition of Mg and B. The horizontal axis represents the S content, and the second vertical axis (right side) represents the total amount of additives. The following relational formula (3) was found to be the condition for almost no deterioration of mechanical properties due to pickling. [Equation (3)] 100Mg+220B-2500S≧-1.2 Here, the element symbols in the formula indicate the content of each element in mass %.

[0042] The addition of B improves intergranular corrosion resistance, as shown in the results of Experiment 2 above. In addition, the addition of B improves the strength of the grain boundaries. Therefore, it was presumed that even if the grain boundaries are corroded, the growth of cracks during tensile tests would be suppressed.

[0043] Moreover, Fig. 6 shows the effect on mechanical properties when Mo and B are added in combination. The horizontal axis is the B content, and the vertical axis is the Mo content. From these results, the following relational formula (4) was found to be the condition for almost no deterioration of mechanical properties due to pickling. [Equation (4)] Mo+0.61×ln(natural logarithm)B ≧-2.0 Here, the element symbols in the formula indicate the content of each element in mass %.

[0044] As shown by the results of Experiment 2 above, the addition of appropriate amounts of B and Mo improves intergranular corrosion resistance.

[0045] In Figure 7, the results when Ca and REM, other sulfide-forming elements, were added together with Mg are plotted with "◇" and "□". The horizontal axis represents the S content, and the second vertical axis (right side) represents the total amount of additives. The following relational equation (5) was found to be the condition for almost no deterioration of mechanical properties due to pickling. [Equation (5)] 100Mg+500Ca+400REM-2500S≧-1.3 Here, the element symbols in the formula indicate the content of each element in mass %.

[0046] As obtained in the above Experiment 2, by containing at least one of Ca and REM in addition to Mg, the corrosion depth of the grain boundaries due to pickling was reduced, and the deterioration of the TS ratio was suppressed.

[0047] (Composition of heat-resistant alloys) The reasons for limiting the composition of the heat-resistant alloy according to this embodiment will be described below. In the following description, unless otherwise specified, "%" representing the composition means "% by mass."

[0048] C: 0.001 to 0.050% C is an essential element for heat-resistant alloys to ensure strength. For this reason, it is necessary to add 0.001% or more. On the other hand, adding a large amount of C causes sensitization during welding and deteriorates intergranular corrosion resistance, so it is necessary to add 0.050% or less. Preferably, the C content is 0.002% or more, and preferably, the C content is 0.030% or less. More preferably, the C content is 0.003% or more, and more preferably, the C content is 0.015% or less.

[0049] Silicon: 0.05 to 0.70% Silicon is an important element that has a deoxidizing effect and contributes to oxidation resistance. To achieve the above effect, it is necessary to include 0.05% or more of silicon. On the other hand, excessive addition of silicon deteriorates weldability, so the upper limit of silicon content is set to 0.70%. The silicon content is preferably 0.08% or more, and more preferably 0.50% or less. More preferably, the silicon content is 0.10% or more, and more preferably 0.40% or less.

[0050] Mn: 0.10-1.0% Mn is a deoxidizing material and must be contained in an amount of 0.10% or more to obtain this effect. On the other hand, excessive content forms MnS. Not only does MnS act as the starting point of corrosion, but MnS is more easily dissolved at high temperatures than MgS or CaS. As a result, S is redissolved in the matrix at the weld, degrading intergranular corrosion resistance. Therefore, the upper limit of the Mn content is 1.0%. Preferably, the Mn content is 0.20% or more, and preferably, the Mn content is 0.80% or less. More preferably, the Mn content is 0.30% or more, and more preferably, the Mn content is 0.50% or less.

[0051] P:0.035% or less P is an element that is inevitably mixed into the alloy as an impurity. It is prone to segregation at grain boundaries and reduces hot workability, so it is necessary to reduce it as much as possible. Furthermore, if a large amount of P is contained, it segregates during weld solidification and is prone to solidification cracking. Furthermore, the area where P is concentrated has poor corrosion resistance. Therefore, the upper limit of the P content is set to 0.035%. Preferably, the P content is set to 0.030% or less. More preferably, the P content is set to 0.025% or less. However, excessive reduction leads to increased processing costs, so it is preferable to set the lower limit of the P content to 0.001%.

[0052] S: 0.0013% or less S is an element that deteriorates hot workability, deteriorates intergranular corrosion resistance, and increases solidification cracking susceptibility during welding. Therefore, it is better to keep the S content as low as possible within cost limits, and it is necessary to reduce the S content to 0.0013% or less. The lower limit may be 0. Preferably, the S content is 0.0011% or less. More preferably, the S content is 0.0009% or less. Here, the S content is a value that includes not only the dissolved S in the alloy but also S as sulfides. The process of forming sulfides will be described later.

[0053] Cr: 19.0~25.0% Cr is an element that improves intergranular corrosion resistance. It also forms dense oxide scale in high temperature environments, suppressing high-temperature oxidation. Therefore, a content of 19.0% or more is necessary. Excessive Cr content causes excessive formation of surface oxide scale, which leads to poor adhesion and deterioration of oxidation resistance. In addition, the stability of the austenite phase decreases, so the upper limit of the Cr content is 25.0%. Preferably, the Cr content is 19.5% or more, and preferably, the Cr content is 24.0% or less. More preferably, the Cr content is 20.0% or more, and more preferably, the Cr content is 23.5% or less.

[0054] Mo: 2.00-4.00% or less Mo has the effect of suppressing the erosion of grain boundaries during acid immersion. It also has the effect of increasing high-temperature strength. Therefore, a content of 2.00% or more is necessary. On the other hand, excessive content easily forms σ phase, which deteriorates hot workability, and also forms σ phase in the heat-affected zone during welding, which promotes grain boundary erosion during pickling. The upper limit of the Mo content is 4.00%. Preferably, the Mo content is 2.50% or more, and preferably, the Mo content is 3.50% or less. More preferably, the Mo content is 2.80% or more, and more preferably, the Mo content is 3.30% or less.

[0055] Cu:1.0~3.5% or less Cu is an element that contributes to improving corrosion resistance in reducing acids such as sulfuric acid. Therefore, a content of 1.0% or more is necessary. On the other hand, it may deteriorate corrosion resistance in a solution containing an oxidizing acid such as nitric hydrofluoric acid. Therefore, when Cu is contained, the Cu content is 3.5% or less. Preferably, the Cu content is 1.6% or more, and preferably, the Cu content is 3.0% or less. More preferably, the Cu content is 1.8% or more, and more preferably, the Cu content is 2.5% or less.

[0056] Ti: 0.10-1.50% Ti is an element that promotes the formation of a dense film and improves oxidation resistance. This effect can be obtained by adding 0.10% or more of Ti. On the other hand, excessive addition causes surface defects due to the formation of a large amount of carbonitrides. Furthermore, it causes defects during welding, particularly black spots on the bead. Therefore, the upper limit of the Ti content is set to 1.50%. Preferably, the Ti content is 0.30% or more, and preferably, the Ti content is 1.00% or less. More preferably, the Ti content is 0.50% or more, and more preferably, the Ti content is 0.80% or less.

[0057] Al: 0.01 to 0.50% Al is an important element having a deoxidizing effect. It functions to control the oxygen concentration, the S content, and the Mg and Ca contents required for fixing S as sulfides. This function will be described later. Furthermore, Al is an element that promotes the formation of a dense oxide film in a high-temperature environment, improving oxidation resistance. On the other hand, excessive addition causes defects during welding. When the Al content in the alloy exceeds 0.50%, the composition of the inclusions becomes Al2O3 (alumina), forming clusters and generating black spots during welding. For the above reasons, the Al content is in the range of 0.01 to 0.50%. Preferably, the Al content is 0.03% or more, and preferably, the Al content is 0.30% or less. More preferably, the Al content is 0.05% or more, and more preferably, the Al content is 0.20% or less.

[0058] B: 0.0001 to 0.0060% B is an element that easily segregates at grain boundaries. When S is contained, it has the effect of lowering the S concentration at grain boundaries by competitive segregation with S. Secondarily, it has the effect of suppressing grain boundary erosion during pickling. This effect is effectively manifested in the alloy according to this embodiment, for example, in a portion that has been welded, that is, a portion that has been melted and solidified again. Furthermore, when Mo, an element with excellent acid resistance, is contained, it has the effect of making Mo act more effectively by simultaneously containing B. It is also an element that increases the strength of grain boundaries. Therefore, it has the effect of suppressing the progress of cracks when a tensile load is applied under conditions in which the grain boundaries are eroded. On the other hand, since the addition of a large amount increases the solidification cracking sensitivity, the upper limit of the B content is 0.0060%. For the above reasons, the B content is in the range of 0.0001 to 0.0060%. Preferably, the B content is 0.0002% or more, and preferably, the B content is 0.0050% or less. The B content is more preferably 0.0003% or more, and more preferably 0.0040% or less.

[0059] Fe: 22.0-40.0% Fe may not be contained from the viewpoint of corrosion resistance and heat resistance of the heat-resistant alloy. However, since Fe is an element that can be fully utilized even if part of Ni is replaced with Fe, it may be used because it reduces the amount of expensive Ni. However, if Fe is contained in an amount exceeding 40.0%, the corrosion resistance of the alloy may deteriorate, so the Fe content is set to 40.0% or less. If Fe is contained, it is preferable that the Fe content is 22.0% or more. Preferably, the Fe content is 25.0% or more, and preferably, the Fe content is 38.0% or less. More preferably, the Fe content is 28.0% or more, and more preferably, the Fe content is 35.0% or less.

[0060] Mg: 0.0003~0.0180% Mg combines with S and fixes S as MgS, thereby rendering S harmless. To obtain this effect, Mg must be added in an amount of 0.0003% or more. On the other hand, even if Mg is added in an amount exceeding 0.00180%, the effect of rendering S harmless is saturated, and excessive addition of Mg reduces hot workability and ductility. Furthermore, it causes blisters and black spots during welding. Therefore, the Mg content is set to a range of 0.0003 to 0.0180%. Preferably, the Mg content is 0.0005% or more, and preferably, the Mg content is 0.0100% or less. More preferably, the Mg content is 0.0009% or more, and more preferably, the Mg content is 0.0050% or less.

[0061] O: 0.0050% or less O is an impurity element that is inevitably mixed into the alloy. It increases the number of oxide-based nonmetallic inclusions and causes surface defects. In addition, if it exceeds 0.0050%, the desulfurization ability is weakened, the S content exceeds 0.0013%, and the hot workability is deteriorated. Therefore, the O content is set to 0.0050% or less. However, since excessive deoxidization leads to an increase in costs, it is preferable that the lower limit of the O content is about 0.0001%. Preferably, the O content is 0.0040% or less. More preferably, the O content is 0.0030% or less.

[0062] <Fixation of S by formation of sulfides> The fixation of S by Mg and Ca, which will be described later, occurs as follows. In this embodiment, CaO-SiO2-Al2O3-MgO-F slag is used when refining the molten alloy. The Al2O3 formed by Al added as a deoxidizer can be effectively absorbed in the slag to control the oxygen concentration in the alloy. This is represented by the following reaction formula (6). In the following reaction formula, [M] indicates that element M is dissolved in the molten alloy, and (R) indicates that a substance of chemical formula R is contained in the slag. [Reaction scheme (6)] 2[Al]+3[O]=(Al2O3) In addition, as the deoxidation progresses, sulfides are formed according to the following reaction formula, and the S concentration in the molten alloy decreases. [Reaction scheme (7)] 2[Al]+3(CaO)=3[Ca]+(Al2O3) [Reaction scheme (8)] 2[Al]+3(MgO)=3[Mg]+(Al2O3) [Reaction scheme (9)] 2[Al]+3[S]+3(CaO)=3(CaS)+(Al2O3) [Reaction scheme (10)] 2[Al]+3[S]+3(MgO)=3(MgS)+(Al2O3)

[0063] The sulfides formed at this time remain not only in the slag but also partially in the molten alloy. However, as long as they exist as sulfides, they are not harmful in this embodiment. By controlling the above-mentioned Al content, the total S content in the alloy, that is, the sum of the content of dissolved S and S in sulfides, can be controlled to 0.0013% or less. At the same time, it is also possible to control the Mg content in the same way. Similarly, REM also forms sulfides, but the content range can be controlled by deoxidation and desulfurization with Al.

[0064] The heat-resistant alloy of this embodiment preferably contains the following optional elements in addition to the above essential elements: The optional elements are at least one selected from Ca: 0.00001 to 0.00500% and REM: 0.00001% to 0.00500%.

[0065] Ca: 0.00001 to 0.00500% Ca combines with S to fix S as CaS, thereby rendering S harmless. To obtain this effect, it is necessary to add 0.00001% or more, while the effect of rendering S harmless is saturated even if it is added in excess of 0.00500%, and excessive addition reduces hot workability and ductility. Furthermore, it causes blisters and black spots during welding. Therefore, the Ca content is preferably in the range of 0.00001 to 0.00500%. More preferably, the Ca content is 0.00003% or more, and more preferably, the Ca content is 0.00200% or less. Even more preferably, the Ca content is 0.00004% or more, and even more preferably, the Ca content is 0.00100% or less. Most preferably, the Ca content is 0.00005% or more, and most preferably, the Ca content is less than 0.00020%.

[0066] REM: 0.00001% to 0.00500% REM (rare earth elements) is a general term for 17 elements in the periodic table, including Sc, Y, and lanthanoids. Like Mg and Ca, REMs render S harmless by fixing S as sulfides. To obtain this effect, REM must be added at 0.00001% or more. Excessive addition leads to increased costs and also deteriorates hot workability. Therefore, the REM content is preferably in the range of 0.00001 to 0.00500%. More preferably, the REM content is 0.00003% or more, and more preferably, the REM content is 0.00200% or less. Even more preferably, the REM content is 0.00004% or more, and even more preferably, the REM content is 0.00090% or less. Most preferably, the REM content is 0.00005% or more, and most preferably, the REM content is less than 0.00020%. The REM may be added as a single element such as La or Ce, or in the form of an alloy consisting of multiple elements containing REM. From the viewpoint of cost, it may be added in the form of misch metal or misch metal-Ni alloy.

[0067] The heat-resistant alloy according to this embodiment is composed of the above essential elements and the above optional elements, with the balance being Ni and unavoidable impurities. The unavoidable impurities are not particularly limited, but may include, for example, nonmetallic inclusions other than sulfides. Furthermore, as necessary, the alloying element may contain about 0.4% in total of Co, W, V, Nb, Pb, etc. In addition to satisfying the above composition, the heat-resistant alloy according to this embodiment must also satisfy the following relational expression (1). By satisfying this relationship, the fixation of S by sulfides can be promoted, and the amount of dissolved S can be reduced. [Equation (1)] 100Mg-2500S≧-1.5 Here, the element symbols in the formula indicate the content of each element in mass %.

[0068] Preferably, the relationship 100Mg-2500S≧−1.2 is satisfied. More preferably, the relationship 1.8≧100Mg-2500S≧−1.2 is satisfied. Even more preferably, the relationship 0.5≧100Mg-2500S≧−1.0 is satisfied.

[0069] The heat-resistant alloy according to this embodiment preferably satisfies the following relational expression (2): As shown in the above Experiment 1, excellent properties can be obtained by estimating the amount of dissolved S from the total S (%S) and the amount of sulfide SS and controlling the amount. [Equation (2)] (%S) / SS<100 Here, (%S) is the total S content based on mass%, and SS is the total S content based on mass%. 2 The amount of sulfides is calculated by multiplying the number density of sulfides per unit area by the square of the sulfide diameter in mm. It is more preferable that the relationship (%S) / SS<90 is satisfied, and it is even more preferable that the relationship (%S) / SS<80 is satisfied.

[0070] The heat-resistant alloy according to the present embodiment preferably satisfies the following relational expression (3). As shown in the above Experiment 3, the inclusion of B under the condition that S is fixed by Mg or the like has the effect of suppressing grain boundary erosion, particularly of the bead portion, during pickling, and further has the effect of improving grain boundary strength. In addition, it has the effect of suppressing the growth of cracks originating from the grain boundary erosion portion when a load such as tension is applied. [Equation (3)] 100Mg+220B-2500S≧-1.2 Here, the element symbols in the formula indicate the content of each element in mass %.

[0071] More preferably, the relationship 3.1≧100Mg+220B−2500S≧−1.0 is satisfied, and even more preferably, the relationship 1.0≧100Mg+220B−2500S≧−0.9 is satisfied. [Equation (4)] Mo+0.61×lnB≧-2.0 Here, the element symbols in the formula indicate the content of each element in mass%. ln is the logarithm function (natural logarithm).

[0072] More preferably, the relationship 0.9≧Mo+0.61×lnB≧−1.7 is satisfied, and even more preferably, the relationship 0.2≧Mo+0.61×lnB≧−1.4 is satisfied.

[0073] The heat-resistant alloy according to the present embodiment may contain at least one of Ca and REM in addition to Mg. In this case, it is preferable that the composition is within the above range and satisfies the following relational expression (5), since this can further suppress the erosion of the grain boundaries of the bead portion during welding. [Equation (5)] 100Mg+500Ca+400REM-2500S≧-1.3 Here, the element symbols in the formula indicate the content of each element in mass %.

[0074] More preferably, the relationship 6.3≧100Mg+500Ca+400REM-2500S≧−1.2 is satisfied, and even more preferably, the relationship 1.1≧100Mg+500Ca+400REM-2500S≧−1.0 is satisfied.

[0075] (Method of manufacturing heat-resistant alloys) Next, a manufacturing method of the heat-resistant alloy according to the present embodiment will be described. The alloy having the above-mentioned composition is not particularly limited. The following manufacturing method is preferable. The heat-resistant alloy according to the present embodiment is preferably an austenitic Ni-Cr-Fe alloy based on the above-mentioned composition. The heat-resistant alloy according to the present embodiment is obtained by melting raw materials such as iron scrap, stainless steel scrap, ferronickel, and ferrochrome in an electric furnace to obtain a molten alloy. The obtained molten alloy is decarburized and refined by blowing a mixed gas of oxygen and rare gas in an AOD (Argon Oxygen Decarburization) furnace or a VOD (Vacuum Oxygen Decarburization) furnace. In addition, quicklime, Fe-Si alloy, Al, etc. are added to reduce Cr oxides in the slag, and then fluorite is added to form CaO-SiO2-Al2O3-MgO-F slag for deoxidization and desulfurization. Optionally, when REM is added, it is added in the form of a Ni-based alloy, misch metal, or misch metal-Ni alloy containing at least one of these elements. The reason why CaO-SiO2-Al2O3-MgO-F slag is used is that it can effectively perform deoxidation and desulfurization, as described above. At the same time, in order to efficiently proceed with desulfurization, it is preferable that the slag has a mass ratio of CaO / Al2O3≧0.5 and CaO / SiO2≧5. In addition, it is preferable that the refractory material of the AOD furnace or VOD furnace is magnesite or dolomite. After refining in the AOD furnace or the like, the composition and temperature are adjusted in the LF process, and then a cast piece (slab) is produced in a continuous casting machine. The method is not limited to a continuous casting machine, and alloy pieces may be produced by the ingot casting-blooming rolling method. In the continuous casting process, the method is particularly preferable, which is called the vertical type, and does not bend the material in the device until solidification is completed after casting. The reason is that the distribution of precipitates is more symmetrical in the plate thickness direction.

[0076] In this embodiment, the cast or alloy flake is hot rolled, and if necessary, cold rolled to obtain a product. In this manner, it is preferable to obtain various products such as thin plates, thick plates, shaped materials, bars, wire rods, etc. It is preferable to subject the hot-rolled alloy material produced by hot rolling to a solution heat treatment, followed by cold rolling to obtain a cold-rolled alloy material, which is then subjected to a final annealing and pickling process to obtain a product. EXAMPLES

[0077] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to these examples as long as it does not exceed the gist of the present invention. First, raw materials such as stainless steel scraps, heat-resistant alloy scraps, and pure nickel, which were adjusted to a predetermined ratio, were melted in an electric furnace to obtain a molten alloy. The obtained molten alloy was decarburized and refined in an AOD furnace, and quicklime, fluorite, Al, Si, etc. were added to perform desulfurization and deoxidization treatment. After that, when REM was to be contained, a predetermined amount of Ni-based alloy containing REM was added. After that, in the LF process, various component compositions shown in Tables 3 and 4 were adjusted, and then the slabs were made by continuous casting. The compositions of C and S shown in the tables were measured by oxygen flow combustion-infrared absorption method using a carbon-sulfur simultaneous analyzer. The composition of N was measured by inert gas-impulse heating and melting method using an oxygen-nitrogen simultaneous analyzer. The components other than those mentioned above were analyzed using X-ray fluorescence analysis. Note that "-" in the table indicates that no intentional addition was made.

[0078] Next, the slab was hot-rolled to obtain a hot-rolled alloy sheet, and the hot-rolled alloy sheet was repeatedly cold-rolled and heat-treated to obtain a cold-rolled coil with a thickness of 2 mm. The cold-rolled coil was finally annealed at 1150°C for 1 minute. A sheet was cut out from the cold-rolled coil and butt-welded. The welding conditions were the same as in Experiment 2. TIG welding was performed with an I groove, the welding current was 150A, the welding speed was 250cm / min, and Ar gas was used as the shielding gas on both the front and back sides.

[0079] After welding, descaling was performed using nitric hydrofluoric acid. The nitric hydrofluoric acid immersion conditions were the same as in Experiment 4. The test pieces were immersed in an aqueous solution of 1.5M nitric acid and 1.5M hydrofluoric acid at 50°C for 48 hours.

[0080] Tensile test pieces of JIS 13B including the welded part were taken from each plate before and after immersion in nitric hydrofluoric acid. The method of taking the test pieces was the same as in Experiment 4, and the test pieces were processed so that the weld line was located at the center of the test piece perpendicular to the longitudinal direction.

[0081] The mechanical properties of the test pieces after pickling were evaluated from the tensile strength ratio (TS ratio) before and after pickling. The judgment of the TS ratio was the same as in Experiment 4. The symbol "◎" in Tables 3 and 4 indicates that the TS ratio is greater than 0.90 and there is almost no deterioration of the mechanical properties due to pickling. The symbol "◯" indicates that the TS ratio is in the range of 0.70 to 0.90 and there is little deterioration of the mechanical properties due to pickling. The symbol "×" indicates that the TS ratio is less than 0.70 and there is deterioration of the mechanical properties due to pickling. The TS ratio of 0.7 or more was determined as an inventive example, and that of less than 0.7 was determined as a comparative example. The results are shown in Tables 5 and 6. The values ​​of the above relational expressions (1) to (5) are also shown in Tables 5 and 6. In addition, "-" in the tables indicates that the calculation was not possible.

[0082] [Table 3]

[0083] [Table 4]

[0084] [Table 5]

[0085] [Table 6]

[0086] The alloys of samples No. 1 to No. 32 in the table are inventive examples that satisfy the conditions of this embodiment, and show little deterioration in mechanical properties after pickling. Among them, materials that satisfy a component composition that satisfies any one of the relations (2) to (5) show especially little deterioration. On the other hand, Samples Nos. 33 to 35 do not satisfy the relational expression (1). Therefore, the grain boundaries were deeply corroded by pickling, and the mechanical properties after pickling were deteriorated. Sample No. 35 also had too high a S content and did not satisfy the relation (1). These samples had significant grain boundary corrosion and the mechanical properties after pickling were deteriorated. Sample No. 35 also had cracks in the bead. Sample No. 36 had too high a C content, which resulted in significant sensitization to corrosion, significant erosion of the HAZ due to pickling, and deterioration of mechanical properties after pickling. Sample No. 37 had too high an O content. In other words, the deoxidation was weak, and the S content was too high due to the weak desulfurization, which caused the grain boundaries to be significantly corroded by pickling. Sample No. 38 had too much Al content, which caused blisters in the welded area, which were corroded during pickling and became the starting point for cracks during the tensile test. Sample No. 39 had too much Mg content, which caused blisters in the welded area, which were corroded during pickling and became the starting point for cracks during the tensile test. Sample No. 40 had too low a Mg content, which reduced the adhesion of S. Although the formula (1) was satisfied, the grain boundaries were eroded and the tensile properties were poor. Sample No. 41 had too high a B content. The weld suffered solidification cracking. Sample No. 42 had too low a B content, which resulted in poor hot workability and made it impossible to manufacture products with a good yield. Sample No. 43 had too low a Mo content, which caused the grain boundaries to be corroded during pickling, resulting in poor mechanical properties after pickling. Sample No. 44 had too high a content of Mo. It had poor hot workability and poor mechanical properties after pickling due to the formation of σ phase in the welded part. [Industrial Applicability]

[0087] Thus, the heat-resistant alloy of the present invention has excellent mechanical properties after welding and pickling, and is suitable for use as a material for members and structures that require welding, and is therefore industrially useful.

Claims

1. By mass, C: 0.001-0.050%, Si: 0.05-0.70%, Mn: 0.10-1.0%, P: 0.035% or less, S: 0.0013% or less, Cr: 19.0-25.0%, Mo: 2.00-4.00%, Cu: 1.0 to 3.5%, Ti: 0.10 to 1.50%, Al: 0.01-0.50%, B: 0.0001 to 0.0060%, Fe: 22.0-40.0%, Mg: 0.0003 to 0.0180%, N: 0.020 or less, and O: 0.0050% or less Contains Optionally, Contains at least one selected from Ca: 0.00001 to 0.00500% and REM: 0.00001% to 0.00500%, The balance is Ni and unavoidable impurities. The heat-resistant alloy has a composition satisfying the following relational formula (1): [Relationship (1)] 100Mg-2500S≧-1.5 Here, the element symbols in the formula indicate the content of each element in mass %.

2. Total S content (%S) based on mass% and 1mm 2 2. The heat-resistant alloy according to claim 1, wherein the amount of sulfides SS calculated by multiplying the number density of sulfides per unit area by the square of the sulfide diameter in mm satisfies the following relational expression (2): [Relationship (2)] (%S) / SS<100

3. The heat-resistant alloy according to claim 1, wherein the composition satisfies the following relational expression (3): [Relationship formula (3)] 100Mg+220B-2500S≧-1.2 Here, the element symbols in the formula indicate the content of each element in mass %.

4. The heat-resistant alloy according to claim 1, wherein the composition satisfies the following relational expression (4): [Relationship (4)] Mo+0.61×lnB≧-2.0 Here, the element symbols in the formula indicate the content of each element in mass%. ln is the logarithm function (natural logarithm).

5. Contains at least one of Ca and REM, The heat-resistant alloy according to claim 1, wherein the composition satisfies the following relational expression (5): [Relationship (5)] 100Mg+500Ca+400REM-2500S≧-1.3 Here, the element symbols in the formula indicate the content of each element in mass %.

6. A method for producing a heat-resistant alloy according to any one of claims 1 to 5, The alloy composition is adjusted by heating and melting the alloy raw materials, followed by refining, casting the resulting molten alloy to obtain a slab, hot rolling the resulting slab to obtain a hot-rolled alloy plate, and optionally cold rolling the hot-rolled alloy plate to obtain a cold-rolled alloy plate. In the refining, a mixed gas of oxygen gas and argon gas is blown into the heated and melted alloy raw material to decarburize it, and the nitrogen content is controlled to 0.01 mass% or less, followed by Cr reduction. Then, a CaO source containing aluminum and fluorite is added to the molten alloy to produce CaO-SiO 2 -Al 2 O 3 - A method for producing a heat-resistant alloy by forming a MgO-F based slag and then optionally adding raw materials containing REM.

Citation Information

Patent Citations

  • HIGH Ni ALLOY EXCELLENT IN INTERGRANULAR CORROSION RESISTANCE AND CORROSION RESISTANCE

    JP2018111846A

  • HIGH Ni ALLOY AND METHOD FOR PRODUCING HIGH Ni ALLOY

    JP2021070838A

  • Cr-Ni alloy pipe

    JP7498416B1

  • Double pipe and welded joint

    WO2022102183A1

  • HIGH Ni ALLOY EXCELLENT IN WELD HOT CRACKING RESISTANCE

    JP2022163586A